2013
DOI: 10.7860/jcdr/2013/7528.3633
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Dental Injuries and Its Relation to Overweight among Indian School Children Living in an Urban Area

Abstract: Aim: The aim of the present study was to determine the prevalence of traumatic dental injuries to permanent incisors and explore the association between dental trauma and overweight in a sample of school children residing in an urban area. Our hypothesis was that there was a significant association between overweight and the presence of dental trauma among urban children. Material and Methods:This cross-sectional survey included 858 school children aged 10-12 years, of both sexes, randomly selected from 12 sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…Past point prevalence studies have reported odds ratios ranging from 0.7 to 3.8 times for TDI among obese children. 20 , 21 , 35 A meta-analysis by CorrÃa-Faria et al showed a pooled odds ratio of 1.3 for TDIs among obese children without special needs, which correlates with the present study result. 22 …”
Section: Discussionsupporting
confidence: 90%
“…Past point prevalence studies have reported odds ratios ranging from 0.7 to 3.8 times for TDI among obese children. 20 , 21 , 35 A meta-analysis by CorrÃa-Faria et al showed a pooled odds ratio of 1.3 for TDIs among obese children without special needs, which correlates with the present study result. 22 …”
Section: Discussionsupporting
confidence: 90%